A administração a partir de uma práxis política: a história do festival Latino Americano de la classe obreira e do cinema novo Latino Americano - Dimitri Augusto da Cunha Toledo (2016)
This thesis materializes in the development context of the Latin American cinemanovista movement and of its proposal of resignification of the cinema, like an engaged and militant cinema. In particular, we seek the rescue of the history of the Festival Latinoamericano de la Obrera (Felco), in order to understand how the organization and the management of the festival take place. This understanding was important, since through this experience one can (re) think the aesthetics and the language of the Administration, even serving to construct other paths for the field of organizational studies. One such path may be administration as a political practice. This thesis proposes a historical reflection, based on the felco, in its edition in Brazil, starting from the understanding of history as element of analysis. Oral history was used as a methodological instrument, which greatly contributed to the enrichment of a dialectical interpretation of history. Felco's story proved to be an important element, since the festival became, to some extent, a reference to other militant cinema practices that did not focus on a market perspective on cinema, but an ideological and political conception of organization, Distribution and display. We hope that this thesis has presented the voices coming from an experience of non-hegemonic organization, which was Felco. In this sense, it also contributed to the approximation between the field of cinema and More particularly in the field of organizational studies, in a period of cinema markedly established by another aesthetic (the aesthetics of hunger), which proposed to think its language beyond the mold of the market, bringing to light people who are often Forgotten by official stories. In this attempt, from another look, it was tried to broaden the understanding about the political administration, mainly from the elaboration of the UFBA group. In order to do so, we proceeded from the understanding of politics anchored in its historical character, showing, through categories ranging from appearance to essence, from the singular to the universal, from the abstract to the concrete, and vice versa. In this way, the political administration must establish itself from the "dialectical relation" that can have other historical forms. It is understood, therefore, that the political administration is between the material production and the reproduction of the human life. Even because it is inexorable for the researcher to link his ideological identity to work. Another contribution of this work is the option for oral history. Notably, oral history has been gaining ground in organizational studies and the expansion of this use makes it possible to echo voices that were silenced by official stories, or rather, told by the ruling class.